2017
DOI: 10.3390/molecules22030505
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antivirals: Natural Products Targeting Replication Enzymes of Dengue and Chikungunya Viruses

Abstract: Dengue virus (DENV) and chikungunya virus (CHIKV) are reemergent arboviruses that are transmitted by mosquitoes of the Aedes genus. During the last several decades, these viruses have been responsible for millions of cases of infection and thousands of deaths worldwide. Therefore, several investigations were conducted over the past few years to find antiviral compounds for the treatment of DENV and CHIKV infections. One attractive strategy is the screening of compounds that target enzymes involved in the repli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 68 publications
(114 reference statements)
1
22
0
1
Order By: Relevance
“…All 36 proteins were expressed at a higher level in patients infected with DENV compared to healthy controls. 52 Huang et al 2018 in his study that the CCL2 CX CL9, IP-10, CXCL11, IL-8, and IL-10 serum levels were significantly higher in the group of patients infected DENV during the first two weeks compared to the control group. 29 The majority of DENV-infected patients make a full recovery after the febrile period and do not enter the critical phase of the disease.…”
Section: Mcp-1/ccl2mentioning
confidence: 93%
“…All 36 proteins were expressed at a higher level in patients infected with DENV compared to healthy controls. 52 Huang et al 2018 in his study that the CCL2 CX CL9, IP-10, CXCL11, IL-8, and IL-10 serum levels were significantly higher in the group of patients infected DENV during the first two weeks compared to the control group. 29 The majority of DENV-infected patients make a full recovery after the febrile period and do not enter the critical phase of the disease.…”
Section: Mcp-1/ccl2mentioning
confidence: 93%
“…Natural products derived from plants have been successfully used to treat a variety of vector borne diseases, such as malaria. Natural products fundamentally differ from synthetic compounds in both chemical scaffolds and mechanisms of 370 action, and have great potential for the development of antiviral agents [152,153]. Oxidative stress has also been reported to play an important role in the pathogenesis of both RNA and DNA viruses [154].…”
Section: Other Approachesmentioning
confidence: 99%
“…Due to the lack of antivirals currently available, several groups have been investigating natural products and medicinal plants as a resource for combating these viruses. These products have a long history as part of traditional medicines and diets [ 95 , 96 ]. While not necessarily predictive of actual consumption, in vitro studies have revealed potential antiviral effects associated with several common food items.…”
Section: Influence Of Nutrition On Reservoir and Secondary Amplificatmentioning
confidence: 99%